Zginanie i Drgania Rusztów Kratowych - Świtka, R. (Engineering Transactions, 1974)
Three types of grids forming regular, rectangular lattices are discussed in the paper; the grids consist of trusses with parallel chords and regular lattices. The grid is described by partial! Difference equations (bending) and by difference-differential equations (vibration). For gridworks which are simply supported along the edges, the solutions have the form of double Fourier series. The solution is given for each type of gridwork and gives its deflection for various load types and the corresponding formulae for free vibration frequencies. Forced vibration, harmonic in particular, is also discussed. A numerical example is given.